Political Discourses on Ukraine-Russia Conflict: A Critical Discourse Analysis of Selected Press Conference at G20 Summit, 2023 - Dildar Ahmed; Dr. Raza-E-Mustafa; Iftkhar Ahmad; Qamar Abbas (Journal of Peace, Development and Communication, 2024)
This study examines the press conference of the American Secretary of State on March 2, 2023 during the course of ongoing G20 Summit in India, in the context of Ukraine-Russia conflict. Antony J. Blinken Secretary of State addressed the press conference generally on global issues and especially on Russian attack on Ukraine. The data has been taken from https://www.state.gov/secretary-antony-j-blinken-at-a-press-availability-30/. Which consists on 21 paragraphs and 1590 words other than Question-Answer session. Clauses are the fundamental building block of transitivity analysis. To accomplish this, a convenient sample of the clauses related to the Ukraine-Russia conflict from the text is taken for analysis. The section of the American Secretary of State’s news conference on the Ukraine-Russian crisis at the G20 summit in India in 2023 is analyzed using the methodology developed by Fairclough and Halliday for Critical Discourse Analysis (CDA) and Transitivity Analysis. The themes of peace and war, aggression and food insecurity of the world because of said crisis, and ideologies of owning and othering are analyzed. Participants, different process types, and circumstances were all carefully examined. Key findings demonstrated that speakers most typically depict activities and occurrences in the physical world via the material process of transitivity. The conclusive results show the American construction as champion of peace and Russia as oppressor, aggressor, and invader.